2017
DOI: 10.1021/acs.energyfuels.6b03291
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Water Control with Nanoemulsion as Pre-pad Fluid in Hydraulically Fracturing Tight Gas Formations

Abstract: Experimental techniques have been developed to evaluate performance of nanoemulsions as pre-pad fluid for reducing water-cut in tight gas formations with multistage hydraulic fractures. More specifically, an aminopolysiloxane nanoemulsion was prepared and formulated in the laboratory for effective and efficient water control. The water-control mechanisms of nanoemulsions as pre-pad fluid in hydraulic fracturing were identified by performing the scanning electron microscopy (SEM), X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The settlement rates (Equation ( 1)) were measured by the weighing method with a precision balance (the accuracy was 0.0001 g; Shanghai Fangrui Instrument CO., LTD., Shanghai, China). In this test, the settled NCs were separated from the liquid phase by a magnet as seen in Figure 1a-(2), while the magnet did not suck out the unsettled particles in the system as seen in Figure 1a- (1). Additionally, the effect of various factors on the settlement stability of NC-VES were studied by changing the nanoparticle concentration, shear rate, temperature and pH.…”
Section: Property Tests Of the Nc-vesmentioning
confidence: 99%
See 1 more Smart Citation
“…The settlement rates (Equation ( 1)) were measured by the weighing method with a precision balance (the accuracy was 0.0001 g; Shanghai Fangrui Instrument CO., LTD., Shanghai, China). In this test, the settled NCs were separated from the liquid phase by a magnet as seen in Figure 1a-(2), while the magnet did not suck out the unsettled particles in the system as seen in Figure 1a- (1). Additionally, the effect of various factors on the settlement stability of NC-VES were studied by changing the nanoparticle concentration, shear rate, temperature and pH.…”
Section: Property Tests Of the Nc-vesmentioning
confidence: 99%
“…In recent years, unconventional oil and gas resources, especially shale gas and tight oil, have become an important part of the world energy landscape and a substitute resource for conventional oil and gas [ 1 , 2 , 3 , 4 , 5 ]. Hydraulic fracturing technology is one of the key technologies for the efficient development of unconventional reservoirs [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoemulsions have the potential to reduce IFT and, accordingly, the capillary pressure of the reservoir [ 1 ], improve rock wettability [ 1 ], ease the fracturing fluid flow-back [ 21 ], eliminate phase trapping [ 21 , 22 ], and increase the regained gas permeability [ 1 , 21 ]. Accordingly, some researchers have recently demonstrated the applicability of nanoemulsions in enhanced oil recovery (EOR) [ 23 , 24 , 25 ], production enhancement (e.g., well stimulation and remediation, well-bore cleaning, and formation fracturing) [ 26 , 27 , 28 ], and pumping of extra heavy crude oil [ 29 ]. For instance, it has been reported that nanoemulsions can (i) minimize/control water-cut [ 28 ], (ii) create new channels for gas flow (i.e., increase gas permeability) [ 28 ], (iii) increase proppant permeability and, accordingly, lower the initial cleanup pressure [ 30 ], (iv) reduce fingering [ 31 ], (v) enhance the flow-back rates of fracturing fluids [ 31 ], (vi) reduce/eliminate water blocking problems [ 27 ], and (vii) minimize surfactant adsorption to the reservoir rocks [ 1 ], among other beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pad fluid, slurry fluid and displacing fluid consist of fracturing fluid. The difference among three fluids is that pad fluid does not carry proppant but creates main fractures . According to the relative low performance requirement of pad fluid, nanoparticles are suited to be mixed with foamed pad fluid and pumped together into the formation.…”
Section: Introductionmentioning
confidence: 99%
“…The difference among three fluids is that pad fluid does not carry proppant but creates main fractures. 25 According to the relative low performance requirement of pad fluid, nanoparticles are suited to be mixed with foamed pad fluid and pumped together into the formation. Base on above investigations and researches, the aqueous dispersion of iron oxide nanoparticles in this study was used to enhance the heating efficiency of microwave irradiation and stabilize foamed pad fluid at the same time.…”
Section: Introductionmentioning
confidence: 99%